Answer:
Every time you add two odd numbers, the sum is an even number.
Look at these different examples: 5 + 3 = 8, 15 + 7 = 22, 21 + 13 = 34. So the sum of two odd numbers must be even.
Let a and b both represent odd numbers, and let a + b be an even number. Therefore, a + b = b + a, which shows that the sum of two odd numbers is even.
Let (2a + 1) be one odd number, and let (2b + 1) be the other odd number. (2a + 1) + (2b + 1) = 2a + 2b + 2 = 2(a + b + 1). Because 2(a + b + 1) is a multiple of 2, it is an even number.
Step-by-step explanation:
those are the answer choices